2015
DOI: 10.1186/s13041-015-0167-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulated internalization of NMDA receptors drives PKD1-mediated suppression of the activity of residual cell-surface NMDA receptors

Abstract: BackgroundConstitutive and regulated internalization of cell surface proteins has been extensively investigated. The regulated internalization has been characterized as a principal mechanism for removing cell-surface receptors from the plasma membrane, and signaling to downstream targets of receptors. However, so far it is still not known whether the functional properties of remaining (non-internalized) receptor/channels may be regulated by internalization of the same class of receptor/channels. The N-methyl-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 91 publications
0
28
0
Order By: Relevance
“…Our data showed that bath application of either DHPG or NMDA/glycine not only caused significant reductions of NMDARs expressed on neuronal surface but also inhibited NMDAR activity recorded in cell-attached patches [25] . Application of dynamin inhibitory peptide (DIP), Myr-4- …”
Section: Research Highlightmentioning
confidence: 59%
See 4 more Smart Citations
“…Our data showed that bath application of either DHPG or NMDA/glycine not only caused significant reductions of NMDARs expressed on neuronal surface but also inhibited NMDAR activity recorded in cell-attached patches [25] . Application of dynamin inhibitory peptide (DIP), Myr-4- …”
Section: Research Highlightmentioning
confidence: 59%
“…To address this question we conducted investigations by using a combination of electrophysiological, biochemical, and genetic approaches. Our data demonstrate that through activating PKD1, NMDAR endocytosis down-regulates remaining surface NMDARs and thereby inhibits NMDAR-mediated synaptic transmissions [25] .…”
Section: Research Highlightmentioning
confidence: 71%
See 3 more Smart Citations